A taxonomic revision of the genus Nothris Hübner, 1825 (Lepidoptera, Gelechiidae) in the Afrotropical region - Bidzilya, Oleksiy V.; Mey, Wolfram; Rajaei, Hossein; Šumpich, Jan (Zootaxa, 2026)
The Afrotropical species of Nothris are revised, and the genus is re-described, incorporating the Afrotropical species. A total of twelve species are recognized as valid, of which seven are described as new based on morphological and molecular evidences: N. mediofasciata sp. nov. (South Africa and Lesotho), N. tornilineata sp. nov. (South Africa), N. basipunctella sp. nov. (South Africa), N. nigrovenata sp. nov. (South Africa), N. lativalva sp. nov. (South Africa), N. nyangensis sp. nov. (Zimbabwe and South Africa), N. nigrisparsus sp. nov. (South Africa). Additionally, the following taxonomic changes are proposed: Ptychovalva trimaculata Janse, 1960 is combined as Nothris trimaculata (Janse, 1960) comb. nov., Gelechia anagramma Meyrick, 1921 as Nothris anagramma (Meyrick, 1921) comb. nov., and Gelechia leucodoxa Meyrick, 1920 as Schizovalva leucodoxa (Meyrick, 1920) comb. nov. Gelechia (Brachmia) trigella Zeller, 1852 is transferred from family Gelechiidae to Autostichidae (under subfamily Symmocinae) and provisionally classified as Symmoca trigella (Zeller, 1852) comb. nov. Finally, the taxonomic status of Nothris dissidens Meyrick, 1913 is discussed, and the lectotype is designated for Gelechia obruta Meyrick, 1921.